Pengembangan Infografis Berbasis Isu Lingkungan Lokal untuk Meningkatkan Keterampilan Berpikir Kritis dan Pemahaman Konsep Siswa di SMPN 4 SATAP Mootilango - Abdurrahman Mahmud; Masra Latjompoh; Chairunnisa J Lamangantjo (Universitas Negeri Jakarta, 2026)
This study addresses the persistent challenge of low critical thinking skills and inadequate conceptual understanding among junior high school students in science, particularly concerning ecology and biodiversity topics that require contextual relevance. The core gap identified is the lack of integration of contextually relevant and visually engaging teaching materials to support the development of these competencies. The research aimed to develop, validate, and evaluate the effectiveness of infographic-based learning media that integrates local environmental issues to enhance these two competencies in Grade VII students. Employing a Research and Development (R&D) approach, the study utilized the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to systematically design and test the learning product. The implementation phase used a One-Group Pre-test–Post-test Design involving 17 students from a public junior high school located in Gorontalo Regency, Gorontalo Province. The developed media achieved an average expert validation score of 93.74% (Very Valid Category), confirming its quality. Effectiveness analysis using the Normalized Gain (N-Gain) score demonstrated significant improvement in student outcomes: the N-Gain for critical thinking was 0.72 (High Category), and for conceptual understanding, it was 0.77 (High Category). Furthermore, the media was highly practical, with student responses showing an overwhelming 98.1% positive feedback. Given the demonstrated high levels of validity, practicality, and effectiveness, the use of infographic-based learning media that connects abstract scientific concepts with local environmental contexts is proven to be a robust resource for fostering students' critical thinking skills and conceptual mastery in biology education.